2015
DOI: 10.1016/j.jpainsymman.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Physicians' Clinical Predictions of Survival in Patients With Advanced Cancer

Abstract: Physicians tend to overestimate when predicting survival in all palliative care patients, including those receiving chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 35 publications
(31 reference statements)
0
44
1
1
Order By: Relevance
“…There is a growing body of evidence about the accuracy of clinician predictions of survival. In preparation for this review, the authors identified two relevant systematic reviews [10, 11 •• ] and ten further articles published in the last 4 years (summarised in Table 1) [20][21][22][23][24][25][26][27][28][29].…”
Section: Clinical Prognostic Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of evidence about the accuracy of clinician predictions of survival. In preparation for this review, the authors identified two relevant systematic reviews [10, 11 •• ] and ten further articles published in the last 4 years (summarised in Table 1) [20][21][22][23][24][25][26][27][28][29].…”
Section: Clinical Prognostic Estimatesmentioning
confidence: 99%
“…Clinicians' specific predictions range from underestimating by half to a sixfold overestimation [10, 11 •• ]. One large prospective cohort study of 2036 locally advanced or metastatic cancer patients accessing palliative care services found that 45% predictions were overestimates, 35% accurate, and 20% underestimates [20].…”
Section: Clinical Prognostic Estimatesmentioning
confidence: 99%
“…As discussed in Section 2.1, each CPS may have promising performance in speciic setings; however, their accuracy is not satisfactory and is often optimistic [5,16,21]. To cope with these problems, many eforts have been made to develop more accurate prognosis prediction models using known prognostic factors.…”
Section: Objective Prognosis Predictionmentioning
confidence: 99%
“…This may partially result from physicians consistently overestimating life expectancy in oncology patients. 34 In a recent study only 52% of patients with advanced stage pancreatic adenocarcinoma had received a palliative care consultation; however, this consult is associated with decreased use of chemotherapy within 30 days of death, a lower risk of ICU admission, multiple emergency department visits, and multiple hospitalizations. 35 This study was not focused solely on the elderly patient.…”
Section: Patient Selection and The Need For A Multi-disciplinary Apprmentioning
confidence: 99%